2022
DOI: 10.1186/s13244-022-01308-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning image reconstruction algorithm for carotid dual-energy computed tomography angiography: evaluation of image quality and diagnostic performance

Abstract: Objectives To evaluate image quality and diagnostic performance of carotid dual-energy computed tomography angiography (DECTA) using deep learning image reconstruction (DLIR) compared with images using adaptive statistical iterative reconstruction-Veo (ASIR-V). Methods Carotid DECTA datasets of 28 consecutive patients were reconstructed at 50 keV using DLIR at low, medium, and high levels (DLIR-L, DLIR-M, and DLIR-H) and 80% ASIR-V algorithms. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Xu et al [261] reached a similar conclusion, and particularly they found that 40 keV VMIs from DLIR poses better CNR and similar or improved image quality compared to 50 keV VMI from hybrid iterative reconstruction, suggesting that 40 keV VMI DLIR could be a new standard for routine low-keV VMI reconstruction. The study for carotid DECT angiography by Jiang et al [262] also supports the conclusion that DLIR improves the image quality and diagnostic performance of VMIs compared to hybrid iterative reconstruction. This superiority is further confirmed in DECT angiography with reduced iodine dose (200 mgI/kg) in terms of image quality and arterial depiction by Noda et al [243].…”
Section: Image Generation For Clinical Applicationsmentioning
confidence: 63%
“…Xu et al [261] reached a similar conclusion, and particularly they found that 40 keV VMIs from DLIR poses better CNR and similar or improved image quality compared to 50 keV VMI from hybrid iterative reconstruction, suggesting that 40 keV VMI DLIR could be a new standard for routine low-keV VMI reconstruction. The study for carotid DECT angiography by Jiang et al [262] also supports the conclusion that DLIR improves the image quality and diagnostic performance of VMIs compared to hybrid iterative reconstruction. This superiority is further confirmed in DECT angiography with reduced iodine dose (200 mgI/kg) in terms of image quality and arterial depiction by Noda et al [243].…”
Section: Image Generation For Clinical Applicationsmentioning
confidence: 63%
“…Till now, only a few studies have been done to explore the application CTA images of DLIR in carotid and cerebrovascular vessel under lower radiation and contrast dose settings. Also, these studies could not reach a further decrease in image noise compared with the standard-dose protocol with ASIR-V algorithm ( 20 , 38 ). Even if a mean subjective score of 4.18 in our study proved that our carotid and cerebrovascular images were able to meet the diagnostic criteria, further studies to validate its impact on diagnostic accuracy are warranted to confirm its efficacy.…”
Section: Discussionmentioning
confidence: 78%
“…The introduction of deep learning image reconstruction (DLIR) algorithm, incorporating a convolutional neural network, has brought new hope for decreasing image noise, and thus optimizing image quality with a more balanced spatial resolution for CTA ( 18 , 19 ). DLIR provides three selectable strength levels (low, medium and high), and DLIR-high (DLIR-H) has been proved to gain the highest ability for reducing image noise while maintaining spatial resolution of images reasonably well ( 20 - 22 ). In our recent study, compared with an adaptive statistical iterative reconstruction-V (ASIR-V) based protocol, the combination of DLIR-H algorithm and low tube voltage for coronary CTA demonstrated superiority in achieving higher image quality as well as significantly lower radiation and contrast dose ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“… 150 , 151 with the remaining approaches including filter‐based methods as well as hybrid methods. 152 , 153 , 154 , 155 , 156 , 157 To be noted that some models are originally developed, 61 , 62 , 65 , 66 , 68 , 70 , 72 , 73 , 77 , 122 , 153 while some are developed by modifying original models through modifying loss functions, or layers, or extending original models to different domains. 60 , 63 , 64 , 69 , 71 , 72 , 74 , 75 , 76 , 78 , 82 , 84 , 102 , 121 , 123 , 124 , 125 , 147 , 150 , 151 , 152 , 155 , 158 …”
Section: Dl‐based Noise Reduction Methodsmentioning
confidence: 99%